SPECIFICS OF IMPLEMENTATION OF STATE POLICY IN THE SPHERE OF EDUCATION IN RUSSIA - E. Kolesnichenko; Y. Radyukova; Y. Sokolinskaya (Вестник Северо-Кавказского федерального университета, 2022)
The relevance of the topic of the study is determined by the fact that most States of the world have concluded that education is the basis for the development of society, the nation and the State, the guarantee of a decent future. The authors analyzed the main conceptual approaches to defining the essence of the concept of State policy in the field of education, specified the content of this concept, identified and described the existing mechanisms for the implementation of State educational policy. During the study, the authors considered the system of education management on the example of the activities of the Department of Education and Science of one of the cities of Russia to form and implement state policy in the field of education. The main problems of the education system have been identified, which are related to the following aspects. The authors highlighted the main directions of improvement of the state policy in the field of education, which require the use of methods ofprogram-targeted management, ensuring system solutions and rational spending of budgetary funds, as well as marketing approaches, providing extra-budgetary sources of financing.